Passive Earth Pressure Analysis for Unsaturated Soils on Retaining Walls Incorporating Arching Effect - Wang, Ding-Jian; Fan, Zhi-Qiang; Wang, Qian-Yun; Wen, Tao; Zhang, Ya-Hui (Civil Engineering Journal, 2025)
Retaining structures in geological and geotechnical engineering are often embedded in unsaturated soil strata. Conventional methods for calculating earth pressure in unsaturated soils typically ignore the rotation of principal stresses in the backfill, a phenomenonknown as the soil arching effect. This study presents a novel analytical framework for determining the passive earth pressure in unsaturated soils that explicitly incorporates this arching effect. The proposed model accounts for both principal stress rotation and the hydro-mechanical coupling between matric suction and soil stress under groundwater influence. Based on the shear strength criterion for unsaturated soils, the model assumes a circular-arc trajectory for the rotating major principal stress, and hydrostatic seepage with matric suction distributed linearly with depth. Using a coordinate axis translation technique, quantitative relationships among lateral earth pressure, interlayer shear stress, and vertical stress are established. The force equilibrium equations for a horizontal differential soil element are then solved to derive closed-form expressions for the passive earth pressure distribution and resultant force. Validation against physical model tests and numerical simulations confirms the model’s accuracy and demonstrates its superiority over the extended Rankine theory, which systematically underestimates passive resistance. Parametric studies highlight the influences of groundwater depth, initial matric suction, and soil strength parameters. The proposed framework offers a more realistic and mechanically sound basis for the design of retaining structures in unsaturated soil environments.